High-strength bar reinforced concrete walls: Cyclic loading test and strength prediction. (1st November 2019) - Ni, Xiangyong; Cao, Shuangyin; Liang, Shuai; Li, Yizhu; Liu, Yang
Highlights: The walls with HRB 600 MPa bars were tested by cyclic loading. High-strength bars have little influence on the ductility of walls. The methods predicted the strength of walls with high-strength bars accurately. Abstract: The use of HS (High-Strength) reinforcing bars in walls effectively decreases the required number of reinforcing bars and thus reduces costs. Four concrete wall specimens with aspect ratios of 2 were tested under cyclic loading. Various parameters were investigated, including the yield strength of the reinforcing bars (HRB 600 MPa vs. HRB 400 MPa), axial load ratio (0.1 vs. 0.2) and ratio of shear demand to shear capacity (0.38 vs. 1.25), by comparing the failure characteristics, hysteretic curves, stiffness degradation, ductility and strain of the reinforcing bars. The test results show that, when the nominal strength is the same, the wall reinforced with HRB 600 MPa bars exhibits slightly less flexural strength, initial stiffness, and energy dissipation but a similar ductility compared to the wall reinforced with HRB 400 MPa bars. The higher axial load ratio resulted in an increase in the strength and a reduction in the drift ratio capacity of the walls. The walls with HS reinforcing bars whose ratio of shear demand to shear capacity was 1.25 failed in a mixed mode of shear and flexure and had a low ductility ratio. As part of the study, methods were established to predict the strength and drift ratio capacity of walls reinforced with HS bars. The accuracies of the proposed methods were examined by comparing the predicted results to the test data from this paper and the literature, and the predicted results show good agreement with the existing data.